2015
DOI: 10.1016/j.jvs.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-guided reoperation for neurogenic thoracic outlet syndrome

Abstract: Recurrent/persistent nTOS is an often-vexing problem with challenging solutions. These results demonstrate the utility of a TOS protocol CT scan in providing correlative objective findings and in assisting with reoperative planning. Positive radiographic findings that correlate with patient symptoms inform the decision to reoperate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…[4,9] In cases of reoperation, the TOS surgery is more challenging from a diagnostic and technical standpoint. [21] The patient in our case refused surgery and chose nonsurgical treatment. Thus, we taught him muscle stretching, muscle strengthening, and range of motion exercises that he could perform at home.…”
Section: Discussionmentioning
confidence: 92%
“…[4,9] In cases of reoperation, the TOS surgery is more challenging from a diagnostic and technical standpoint. [21] The patient in our case refused surgery and chose nonsurgical treatment. Thus, we taught him muscle stretching, muscle strengthening, and range of motion exercises that he could perform at home.…”
Section: Discussionmentioning
confidence: 92%
“…[7][8][9][10][11][12][13][14][15][16][17] However, it is estimated that anywhere from 5% to 30% of patients can experience minimal improvement or later symptom recurrence following surgical intervention. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Previous studies have shown that incomplete first rib resection, reattachment of residual scalene muscle, and fibrous scarring around the brachial plexus are most frequently implicated in persistent or recurrent NTOS. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Understanding the principal factors underlying recurrent NTOS is informative regarding the extent to which each of these individual anatomical structures should be prioritized in primary operations.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Previous studies have shown that incomplete first rib resection, reattachment of residual scalene muscle, and fibrous scarring around the brachial plexus are most frequently implicated in persistent or recurrent NTOS. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Understanding the principal factors underlying recurrent NTOS is informative regarding the extent to which each of these individual anatomical structures should be prioritized in primary operations. However, the optimal approach for re-intervention remains unclear and there is little information available regarding overall outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite effective surgical treatment for NTOS, approximately 5% to 30% of patients experience minimal improvement or symptom recurrence during long-term follow-up. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Incomplete operations and perineural scar tissue have been implicated in the development of recurrent NTOS. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Reoperations involving resection of residual scalene muscles and first rib remnants can be safe and effective, as demonstrated in a recent study from our medical center.…”
mentioning
confidence: 99%